2019
DOI: 10.1155/2019/6705424
|View full text |Cite
|
Sign up to set email alerts
|

The Reduced Expression of EOLA1 May Be Related to Refractory Diabetic Foot Ulcer

Abstract: Background. Chronic diabetic foot ulcer (DFU) is one of the most intractable complications of diabetes mellitus (DM). Its pathogenesis is complex, and uncontrolled chronic inflammation is an important factor. Endothelial overexpressed lipopolysaccharide-associated factor 1 (EOLA1) discovered in our laboratory is an intracellular protein with the function of inflammatory regulation. This study was aimed at observing the expression of EOLA1 in DFU skin tissues and its relationship with inflammation and at explor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 24 publications
2
6
0
1
Order By: Relevance
“…Consistent with our findings with MT2 restoration, we found that genetic inhibition of MT2 by intrathecal injection of MT2A siRNA in turn induced mechanical allodynia in normal mice through a similar neuroinflammatory signaling pathway. Our data are in line with previous reports showing a significant relationship between MT2 expression and cell inflammatory responses that act by suppressing NF-κB signaling activation [ 32 , 36 ]. Therefore, MT2 is likely to contribute to oxaliplatin-induced neuropathic pain through the inactivation of the NF-κB signaling pathway in the spinal dorsal horn.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our findings with MT2 restoration, we found that genetic inhibition of MT2 by intrathecal injection of MT2A siRNA in turn induced mechanical allodynia in normal mice through a similar neuroinflammatory signaling pathway. Our data are in line with previous reports showing a significant relationship between MT2 expression and cell inflammatory responses that act by suppressing NF-κB signaling activation [ 32 , 36 ]. Therefore, MT2 is likely to contribute to oxaliplatin-induced neuropathic pain through the inactivation of the NF-κB signaling pathway in the spinal dorsal horn.…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with our ndings with MT2 restoration, we found that genetic inhibition of MT2 by intrathecal injection of MT2A siRNA in turn induced mechanical allodynia in normal mice through a similar neuroin ammatory signaling pathway. Our data are in line with previous reports showing that a signi cant relationship between MT2 expression and cell in ammatory responses that acts by suppressing NF-κB signaling activation [32,36]. Therefore, MT2 is likely to contribute to oxaliplatin-induced neuropathic pain through inactivation of the NF-κB signaling pathway in the spinal dorsal horn.…”
Section: Discussionsupporting
confidence: 92%
“…Aside from the main etiological factors, several factors also have critical roles in the occurrence and processes of DFU, including abnormal gene alterations, immune cell infiltration, and inflammation (4)(5)(6). Wu et al found that the downregulation of endothelium and lymphocyte associated ASCH domain 1 (EOLA1) expression exacerbated DFU by enhancing the inflammatory pathway activity, and also detected differentially expressed genes (DEGs), including metallothionein 2A and interleukin (IL)-6 (6).…”
Section: Introductionmentioning
confidence: 99%